Kualitas Tidur, Kecemasan, Tekanan Darah dan Hubungan pada Kejadian Hipertensi Lansia - Bun Yurizali; Nurmaines Adhyka; Kurnia Maidarmi Handayani; Salsabila Maharani.S (STIKES Ngesti Waluyo, 2025)
Hypertension is a major health problem among the elderly, with rising prevalence. Sleep quality and anxiety contribute to blood pressure regulation, but their relationship is unclear. This study aims to analyze the relationship between sleep quality, anxiety, and blood pressure in hypertensive elderly patients at Puskesmas Air Dingin, Padang City. This study employed an analytical observational design with a cross-sectional approach. The sample included 42 hypertensive elderly patients registered at Puskesmas Air Dingin, selected by consecutive sampling. Data were analyzed using univariate and bivariate analyses, presented in frequency distribution, and processed with SPSS version 25.0. The results showed that most hypertensive elderly patients were aged 60-69 years (73.8%), with an equal gender distribution (50.0% male and female). The majority of respondents had poor sleep quality (83.3%) and mild anxiety (71.4%). No significant relationship emerged between sleep quality and systolic blood pressure (p=0.594), but a significant relationship was found between sleep quality and diastolic blood pressure (p=0.049). Additionally, anxiety was not associated with systolic (p=0.726) or diastolic blood pressure (p=0.647). In summary, poor sleep quality relates to higher diastolic blood pressure, while anxiety does not significantly correlate with blood pressure.